Policy Matters : Regulatory Indicators for Sustainable Energy - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2018)
Sustainable energy is at the heart of the global development and climate change agenda. Reaching the targets set by the United Nation’s Sustainable Development Goal 7 (SDG7) will require a rapid increase in energy access, renewable energy and the efficient use of existing energy resources. Public debate centers on securing adequate finance to meet these global targets, but evidence demonstrates that policy can often be a prerequisite for mobilizing finance. RISE 2018 demonstrates that progress on sustainable energy outcomes has often been preceded by long-term efforts to strengthen policy and regulatory environments. Precisely because policy matters, it is important to track how well countries are doing in creating the regulatory environment needed to accelerate achievement of sustainable energy goals. RISE provides such a global scorecard which summarizes countries’ regulatory environments. It does so by tracking the adoption of good-practice policies with respect to energy access, energy efficiency, and renewable energy at the country level as of December 2017, scoring them on a scale from 1 to 100, and classifying the strength of a country’s policy environment according to a “traffic light” system with green for advanced, yellow for intermediate, and red for early stage. Poor creditworthiness of utilities undermines the sustainable energy agenda. Power utilities are among the central actors in the energy sector in most countries, and their financial health is critical for the viability of investments across the sustainable energy agenda. As of 2016, however, only about half of all power utilities met several basic creditworthiness requirements. Moreover, performance on almost all dimensions of credit-worthiness has deteriorated since 2012. The situation is particularly acute in low-access countries, where the number of utilities meeting basic creditworthiness criteria has dropped, falling from 63 percent in 2012 to 37 percent in 2016. Good institutions and enforcement are also necessary elements to achieve sustainable energy results. Adopting good practice policies will not yield results without strong institutions and consistent enforcement. RISE 2018 has incorporated proxy enforcement indicators to provide some sense of the level of attention that countries are giving to enforcement issues.